Analysis of the Expectation-Confirmation Model in Continuance Intention to Use the MAXIM Application - Hamid, Nisrina (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2025)
The study focuses on analyzing the impact of the Expectation Confirmation Model (ECM) on the intention to continue using the MAXIM app in Kendari city. With 140 respondents selected using purposive sampling, data on perceived usefulness, confirmation, habit, and intention to continue was collected through a questionnaire. Structural Equation Modeling Partial Least Squares (SEM-PLS) was used for data analysis. Results show confirmation strongly influences perceived usefulness and habit, while its impact on satisfaction is weaker. Perceived usefulness and habit positively affect intention to continue usage, with satisfaction also playing a role, albeit weakly. User experience could be a valuable aspect for future research.